Influences on willingness to use vaginal or oral HIV PrEP during pregnancy and breastfeeding in Africa: the multisite MAMMA study. Issue 6 (10th June 2020) - van der Straten, Ariane; Ryan, Julia H; Reddy, Krishnaveni; Etima, Juliane; Taulo, Frank; Mutero, Prisca; Taylor, Jamilah; Piper, Jeanna; Musara, Petina; ,
Abstract: Introduction: Women in sub‐Saharan Africa spend a substantial portion of their reproductive lives pregnant and/or breastfeeding (P/BF), yet they have limited options to prevent HIV during these maternal stages. In preparation for phase 3b prevention trials in P/BF women, we explored attitudes about using a vaginal ring or oral pills for pre‐exposure prophylaxis (PrEP), perceptions of HIV risk during P/BF and key influences on future PrEP use. Methods: In 2018, we conducted 16 single‐sex focus group discussions (FGDs) with community‐ and clinic‐recruited HIV‐uninfected women, currently or recently P/BF, aged 18 to 40, and men with (currently or recently) P/BF partners, aged 18+. Participants completed a behavioural questionnaire, viewed an educational video and handled prototype placebo products. FGDs were conducted in local languages and transcribed, coded and analysed, using a socio‐ecological framework, for key influences on willingness to use products, HIV risk perceptions and opinions on product attributes. Results: Of the 128 participants (65 women, 63 men) 75% lived with their partner and 84% had a child. Women reported the most important influencers when P/BF were partners, and all stated that health decisions when P/BF are typically made jointly (e.g. medication use; ante/postnatal and baby care). There was consensus that P/BF women are at high risk for HIV, primarily because of their partner's infidelities, and new prevention options were welcomed. Participants valued multiple options and stated that woman's personal preference would be key to product choice. Anticipated concerns about products included risk of miscarriage, impact on infant development, complications during delivery and adequate production or taste of breastmilk. Specific perceived disadvantages emerged for the ring (e.g. vaginal discomfort, difficulty inserting/removing) and for pills (e.g. nausea/vomiting) that may be exacerbated during pregnancy. Health care providers' (HCPs) knowledge and approval of product use during P/BF was needed to mitigate anticipated fears. Conclusions: Participants perceived pregnancy and breastfeeding as high HIV risk periods and valued new prevention options. HIV protection of the mother‐child dyad, safety of the baby, and ultimately, health of the family were paramount. Endorsement by HCPs and support from partners were key to future product acceptance. Participants recommended involving partners and HCPs in sensitization efforts for future trials.